Bioprocessing of recombinant proteins from Escherichia coli inclusion bodies: insights from structure-function relationship for novel applications - Kachhawaha K.; Singh S.; Joshi K.; Nain P.; Singh S.K. (My University, 2025)
The formation of inclusion bodies (IBs) during expression of recombinant therapeutic proteins using E. coli is a significant hurdle in producing high-quality, safe, and efficacious medicines. The improved understanding of the structure-function relationship of the IBs has resulted in the development of novel biotechnologies that have streamlined the isolation, solubilization, refolding, and purification of the active functional proteins from the bacterial IBs. Together, this overall effort promises to radically improve the scope of experimental biology of therapeutic protein production and expand new prospects in IBs usage. Notably, the IBs are increasingly used for applications in more pristine areas such as drug delivery and material sciences. In this review, we intend to provide a comprehensive picture of the bio-processing of bacterial IBs, including assessing critical gaps that still need to be addressed and potential solutions to overcome them. We expect this review to be a useful resource for those working in the area of protein refolding and therapeutic protein production. © 2022 Taylor & Francis Group, LLC.